Electrical Conductivity and Dielectric Relaxation in Ag1−xLixNbO3 - Jan Macutkevic; Juras Banys; Antoni Kania (Crystals, 2022)
The broadband electrical properties of Ag1−xLixNbO3 (ALNx) ceramics (x ≤ 0.1) together with AgNbO3 (AN) crystals were studied over a wide temperature interval of 20–800 K. For ALNx with x ≤ 0.05, a very diffused ferroelectric phase transition was observed. The position of the dielectric permittivity maximum in this phase transition is strongly frequency-dependent and is described well by the Vogel–Fulcher law. The freezing temperature decreases when the lithium concentration increases. Below the ferroelectric phase transition temperature, the dielectric dispersion is mainly caused by ferroelectric domain dynamics. Moreover, for ALN3 and ALN5 ceramics at very low temperatures (below 100 K), behavior typical of dipolar glasses is observed. At higher temperatures (above 650 K for ALN5), electrical conductivity effects become important. The DC conductivity increases with temperature according to the Arhenius law and the activation energy is highest in the antiferroelectric phase. Moreover, the activation energy is strongly dependent on the lithium concentration and it is greatest when x = 0.02.